2018
DOI: 10.1007/s13566-017-0339-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BioZorb® surgical marker placement on post-operative radiation boost target volume

Abstract: ObjectiveBioZorb® is a tumor bed marker placed during partial mastectomy for targeted post-operative radiation. This study was designed to evaluate BioZorb® effect on radiation boost clinical target volume (CTV), planning target volume (PTV), median dose to ipsilateral lung (Gy), and heart irradiation in left-sided cancers.MethodsData was collected via a retrospective cohort study with two study arms: BioZorb® intra-operative placement versus no BioZorb® placement. Patients were stratified by BMI, age, tumor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…This corresponds with previously reported study findings from a retrospective cohort study and a casecontrol study, both of which compared patients with and without BZ placement, and both reporting slightly more than a 30 % reduction in PTV or tumor bed volume for patients implanted with the BZ. 37,38 The ROs assessed the BZ as ''very useful'' for 86.6 % of the patients receiving APBI, with 85 % of the ROs reporting a 20 % to 30 % decrease in PTV for these patients. This may be expected given the necessity of precise targeting with APBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds with previously reported study findings from a retrospective cohort study and a casecontrol study, both of which compared patients with and without BZ placement, and both reporting slightly more than a 30 % reduction in PTV or tumor bed volume for patients implanted with the BZ. 37,38 The ROs assessed the BZ as ''very useful'' for 86.6 % of the patients receiving APBI, with 85 % of the ROs reporting a 20 % to 30 % decrease in PTV for these patients. This may be expected given the necessity of precise targeting with APBI.…”
Section: Discussionmentioning
confidence: 99%
“…This marker has been associated with positive cosmetic and overall patient outcomes as well as reduced RT volumes in the few reported studies to date. [36][37][38][39][40][41][42] These studies have been small, focused on RT planning outcomes or limited to short-term follow-up evaluation. This is the first report of 24-month outcomes after BCS with BioZorb Ò (BZ) implantation in a large U.S. registry of data collected across an array of clinical settings.…”
mentioning
confidence: 99%
“…While pain and discomfort have been noted with the Biozorb device, without having a comparison with clips, it is difficult to fault the device versus the surgery performed (and possible subsequent radiation). It was notable that Wiens et al showed a statistically significant increase in the amount of radiation to the ipsilateral lung in the Biozorb arm compared to the traditional surgical clips arm but the long-term impact of this clinically is unknown (Wiens et al, 2018). Thus, clinical outcomes outside the cavity marking abilities of both interventions could not reliably occur given the scarce presence of peer reviewed, reasonable scientific data directly comparing each approach.…”
Section: Incremental Cost-utility Ratio (Icur) and Dominancementioning
confidence: 99%
“…A study performed by Ward et al exhibited Biozorb's presence on a variety of imaging modalities, including mammography, ultrasound, MRI, chest radiography, and CT in an effort to increase awareness over its form and appearance (Ward et al, 2018) A more recent study by Wiens at al. demonstrated the device's ability to reduce clinical target volume and planning target volume of boost radiation post-op with statistically significant results (Wiens et al, 2018). However, the authors noted no difference in the ability of the device to reduce radiation to secondary organs, an in fact noted an increase in ipsilateral lung radiation.…”
Section: Introductionmentioning
confidence: 97%
“…It allows for tissue ingrowth during the healing process and is slowly resorbed by the body over time. Current literature investigating the use of the BioZorb is limited and focused on its value in improving delivery of radiation . The impact of complications associated with placement of the BioZorb in patients who have had partial mastectomies has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%